PERANCANGAN RUANG EDU-REKREASI SAMPAH PLASTIK SEBAGAI USAHA MENGHIDUPKAN KAWASAN PESISIR MUARA ANGKE - Evan Christopher; Nina Carina (Jurusan Arsitektur dan Perencanaan, 2022)
Muara Angke is one of the largest fishing boat harbor areas in Jakarta which is abundant in the potential of its natural resources. However, the potentials that are owned are starting to be closed and less developed. This is due to the pile of garbage in the coastal area of Muara Angke which causes the quality of the surrounding environment to degrade. Piles of garbage regularly come from the flow of 13 rivers in Jakarta which empties into the Jakarta Bay every time the West Wind season arrives. Based on the data, the composition of the existing waste piles is dominated by plastic type waste as much as 46-57%. In addition to the dominating composition of plastic waste, there is also a strong indication of the increasing amount of plastic waste since the pandemic due to changes in people’s behaviour during the pandemic (online shopping, food packaging, etc.). Responding to the existing condition, handling is needed to overcome the environmental degradation that occurs. The handling needed is a treatment that can pull back the movement of the population to the coastal area of Muara Angke. The approach used in this treatment is urban acupuncture. Through the urban acupuncture approach, the location of the intervention that needs to be improved and the types of functions that can be offered are obtained. Keywords: Degradation; Muara Angke; Urban Acupuncture; Waste Abstrak Muara Angke merupakan salah satu kawasan pelabuhan kapal ikan terbesar di Jakarta yang melimpah akan potensi sumber daya alam yang dimiliki. Namun, potensi-potensi yang dimiliki mulai tertutup dan kurang berkembang. Hal ini disebabkan oleh adanya tumpukan sampah di kawasan pesisir Muara Angke yang menyebabkan kualitas lingkungan sekitar mengalami degradasi. Tumpukan sampah rutin hadir dari aliran 13 sungai di Jakarta yang bermuara di teluk Jakarta setiap musim angin Barat tiba. Berdasarkan data, komposisi tumpukan sampah yang ada didominasi oleh sampah jenis plastik sebanyak 46-57%. Selain komposisi sampah plastik yang mendominasi, juga ada indikasi kuat mengenai meningkatnya jumlah sampah plastik semenjak masa pandemi oleh karena perubahan perilaku masyarakat selama pandemi (belanja online, bungkus makanan, dan lain-lain.). Merespon kondisi yang ada, diperlukan penanganan untuk mengatasi degradasi lingkungan yang terjadi. Penanganan yang diperlukan adalah penanganan yang dapat menarik kembali pergerakan penduduk ke kawasan pesisir Muara Angke. Melalui pendekatan urban acupuncture, didapatkan titik lokasi intervensi yang perlu diperbaiki serta jenis fungsi yang dapat ditawarkan.